-15=-11+v

Simple and best practice solution for -15=-11+v equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -15=-11+v equation:


Simplifying
-15 = -11 + v

Solving
-15 = -11 + v

Solving for variable 'v'.

Move all terms containing v to the left, all other terms to the right.

Add '-1v' to each side of the equation.
-15 + -1v = -11 + v + -1v

Combine like terms: v + -1v = 0
-15 + -1v = -11 + 0
-15 + -1v = -11

Add '15' to each side of the equation.
-15 + 15 + -1v = -11 + 15

Combine like terms: -15 + 15 = 0
0 + -1v = -11 + 15
-1v = -11 + 15

Combine like terms: -11 + 15 = 4
-1v = 4

Divide each side by '-1'.
v = -4

Simplifying
v = -4

See similar equations:

| x+500=17.548 | | 20=8+150k | | 4m+9-7m=-3(m-3) | | 5/2*-2 | | -7x+x^9= | | 2(3x-5)=6(x-2) | | 2x+3-5+7=10x+3-6x-4 | | 0.9x-0.2(15-5x)=0.4(x-4) | | 0.36x=26 | | 9/x+1-5/2=8/3x+3 | | .5x-6=.33 | | 10q^2+9q+2= | | .5-6=.33 | | (z-24)/8+2 | | 3x-2(x-1)=4x+20-2x | | 6(x-6)+12=3(x-7) | | 20=k-10 | | 5y^2+12y-32= | | w-3/4=7/4 | | 3x+9xy-30x=0 | | 1/2k+5=k+3 | | 3(a+2)=2(a+3)-3 | | 14x+5y=296 | | (6*-2)+6(2)/6-2 | | 6+5p-2=8p+4-2p | | 8+4x+7=3x+3-5x | | (4m^6+3m^5-6m^7)/m^2 | | c^2a^3b-cab^3=0 | | p-4=-9-p | | 10-9=9+6x-9 | | (4x-2)-(7x+2)= | | 4-25y=29-5y |

Equations solver categories